2016
DOI: 10.1007/s40744-016-0025-3
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Diarrhea Associated with High Teriflunomide Blood Concentration

Abstract: Further studies are needed to establish the optimal therapeutic levels of teriflunomide. However, therapeutic drug monitoring of teriflunomide blood concentrations may be helpful to improve effectiveness and to prevent toxicity in patients taking leflunomide for RA, particularly in those with suboptimal therapeutic response to leflunomide or in patients with toxicity suspected to be induced by leflunomide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In addition, both celiac disease as well as autoimmune thyroiditis and a host of other autoimmune conditions are associated with lymphocytic colitis. 4 Although there have been cases of lymphocytic colitis associated with leflunomide use, 1 it has not been associated with teriflunomide to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, both celiac disease as well as autoimmune thyroiditis and a host of other autoimmune conditions are associated with lymphocytic colitis. 4 Although there have been cases of lymphocytic colitis associated with leflunomide use, 1 it has not been associated with teriflunomide to date.…”
Section: Discussionmentioning
confidence: 99%
“…Teriflunomide is an active form of leflunomide, a drug that is used to treat rheumatoid arthritis. 1 Previous studies have reported gastrointestinal symptoms as a potential adverse effect of teriflunomide, but these symptoms are usually self-limiting and will be alleviated when the drug is eliminated, either through time or washout with cholestyramine. 2…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Duquette et al . also described a case of histologically acute and subacute colitis related to high teriflunomide blood concentration after 2 years of treatment 5 …”
Section: Figurementioning
confidence: 98%
“…A recent manuscript proposed the possibility of teriflunomide promoting a lymphocytic colitis pattern [4]. Finally, Duquette et al also described a case of histologically acute and subacute colitis related to high teriflunomide blood concentration after 2 years of treatment [5].…”
Section: Item Of Correspondencementioning
confidence: 99%
“…While leflunomide is widely used in treating RA, either as a monotherapy or in combination with methotrexate [18], the class of DHODH inhibitors to which both leflunomide and teriflunomide belong have been the subject of numerous safety concerns since their approval by the FDA. Postmarket surveillance includes reports of a variety of drug-related adverse reactions, including elevated liver enzymes and hepatotoxicity, peripheral neuropathy, vasculitis, hypertension, alopecia, pruritus, nausea, and diarrhea [16,[19][20][21][22][23][24][25][26][27][28]. In one prospective study evaluating leflunomide treatment in 136 RA patients, 65% of patients experienced at least that inhibitors of DHODH show immunomodulatory activity, which is most pronounced on T cells [3][4][5][6][7][8], with T helper (Th) 1 and Th17 cells acting as important contributors to the inflammatory processes of RA [9].…”
Section: Key Pointsmentioning
confidence: 99%